Dr. Harka Gurung (Born June 5, 1935-passed away on September 23, 2006) - Malla, U. M. (Himalayan Review, 2009)
Not Available The Himalayan Review Vol. XXXVIII, 2007 (Harka Gurung Memorial Issue) Page: 119-121